2021
DOI: 10.3389/fimmu.2021.768734
|View full text |Cite
|
Sign up to set email alerts
|

Serum Alpha-1-Acid Glycoprotein-1 and Urinary Extracellular Vesicle miR-21-5p as Potential Biomarkers of Primary Aldosteronism

Abstract: Primary aldosteronism (PA) is the most common cause of secondary hypertension and reaches a prevalence of 6-10%. PA is an endocrine disorder, currently identified as a broad-spectrum phenotype, spanning from normotension to hypertension. In this regard, several studies have made advances in the identification of mediators and novel biomarkers of PA as specific proteins, miRNAs, and lately, extracellular vesicles (EVs) and their cargo.AimTo evaluate lipocalins LCN2 and AGP1, and specific urinary EV miR-21-5p an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 88 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…Among the proteins resulting from the fold-change analysis of the EH vs PA comparison, we have found also A1AG1 (AGP1), a protein that is recently attracting attention as a potential biomarker for PA ( 12 , 33 ). A1AG1 is an acute-phase protein associated with inflammation, it has been suggested to indicate increased cardiovascular risk, and its upregulation in uEVs of PA patients may be a consequence of mineralocorticoid activation ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the proteins resulting from the fold-change analysis of the EH vs PA comparison, we have found also A1AG1 (AGP1), a protein that is recently attracting attention as a potential biomarker for PA ( 12 , 33 ). A1AG1 is an acute-phase protein associated with inflammation, it has been suggested to indicate increased cardiovascular risk, and its upregulation in uEVs of PA patients may be a consequence of mineralocorticoid activation ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…This mRNA can interfere with cortisol and aldosterone syntheses binding on the untranslated region of CYP11B1 (11β-hydroxylase) and CYP11B2 (aldosterone synthase) genes ( 36 ). Previously, Carvajal et al ( 37 ) evaluated in PA several mediators and novel biomarkers of chronic inflammation; in a finding that compared normotensive subjects and patients with EH, PA showed higher serum alpha-1-acid glycoprotein-1 (AGP-1) protein [specifically related to aldosterone, renin levels, and aldosterone-to-renin ratio (ARR)] and decreased the expression of miR-21-5p. AGP-1 could be evaluated with a dual role, as a potential biomarker of PA and as a possible mediator of the tissue response to high aldosterone production.…”
Section: Discussionmentioning
confidence: 99%
“…AGP-1 could be evaluated with a dual role, as a potential biomarker of PA and as a possible mediator of the tissue response to high aldosterone production. The downregulation of miR-21-5p could affect the downstream target genes related to inflammation, interleukin-1β (IL-1 β) gene, and fibrotic processes ( 37 ). A study by Nakamura et al ( 38 ) demonstrated that CYP11B1, a steroidogenic enzyme, which converts deoxycorticosterone to corticosterone, was diffusely detected in the APA, and it could play a pivotal role in the tumor genesis.…”
Section: Discussionmentioning
confidence: 99%
“…Orm1 was the only protein with significantly altered expression in each condition. The concentration of Orm proteins in the plasma increases in response to inflammatory stimuli (Baumann and Gauldie, 1990;Alam and Papaconstantinou, 1992;Wigmore et al, 1997;Luo et al, 2015), enabling it to carry out immunoregulatory functions and suggesting that Orm1 may serve as a potential biomarker in different diseases (Baraniuk et al, 2005;Luo et al, 2015;Zhou et al, 2016;Brink et al, 2019;Shu et al, 2020;Carvajal et al, 2021). Orm1 is a transport protein that plays a dual role in regulating inflammation, producing both anti-and pro-inflammatory effects (Taguchi et al, 2013;Smith and Waters, 2018).…”
Section: Orm1 Is Overexpressed In the Spinal Cord And Cortex Of Both ...mentioning
confidence: 99%